Medical Negliegence and Liability of Health Professionals in the European Court of Human Rights Case Law - Murgel, Jasna (Medicine, Law & Society, 2020)
Although the European Convention on Human Rights (ECHR) does not explicitly lay down the right to health, it can be derived from the long-term jurisprudence of the European Court of Human Rights (ECtHR) which interpreted certain provisions of the ECHR (in particular articles concerning the right to life, the prohibition of torture and inhuman conduct and the right to private and family life). Based on the ECtHR jurisprudence it may be concluded that the ECHR, albeit implicitly, refers to the right to health as well. It regulates negative obligations reflected in the prohibition of interference with a certain right. It can also be interpreted as setting positive obligations of the states to ensure the exercise of the right to health, although the extent of that positive obligation is still not fully defined. The present contribution focuses on a single segment of the right to health in the practice of the ECtHR, i.e. the Court’s interpretation of the state’s responsibility for medical negligence, especially in the last few years.
Keywords: state’s responsibility; the right to health; the right to life; prohibition of torture; the right to private and family life